Epstein-Barr virus latent membrane protein 1 is essential for B-lymphocyte growth transformation. - Kaye, K M (1993)
The gene encoding latent-infection membrane protein 1 (LMP1) was specifically mutated in Epstein-Barr virus (EBV) recombinants by inserting a nonsense linker after codon 9 or codon 84 or into an intron 186 bp 3' to the latter insertion site. EBV recombinants with the LMP1 intron mutation were wild type for LMP1 expression and for growth transformation of primary B lymphocytes. In contrast, EBV recombinants with the mutations in the LMP1 open reading frame expressed N-terminally truncated crossreactive proteins and could initiate or maintain primary B-lymphocyte transformation only when wild-type LMP1 was provided in trans by a coinfecting, transformation-defective EBV, P3HR-1. These data indicate that LMP1 is essential for EBV-mediated transformation of primary B lymphocytes, that the first 43 amino acids are critical for LMP1's function, and that codon 44-initiated LMP1 does not have a dominant negative effect on transformation.